Neuro-Ophthalmic Symptoms of Primary Headache Disorders: Why the Patient With Headache May Present to Neuro-Ophthalmology. Issue 2 (June 2019) - Smith, Stacy V.
Abstract : Background: Primary headache disorders can cause many ophthalmic symptoms that lead many patients to present for neuro-ophthalmic evaluation. Neuro-ophthalmologists frequently encounter these patients in clinical practice. Evidence Acquisition: A literature review was completed in PubMed using the following terms paired with "migraine" and "headache:" dry eye, eye pain, monocular diplopia, binocular diplopia, photophobia, visual field defect, tunnel vision, floaters, amaurosis fugax, transient visual obscuration, autonomic symptoms, anisocoria, visual snow, Alice in Wonderland syndrome, and palinopsia. Results: Patients with migraine experience a wide range of visual disturbances including aura and more complex perceptual abnormalities such as Alice in Wonderland syndrome and visual snow. Visual disturbances may consist of positive and/or negative phenomena and may be binocular or monocular. Migraine and other primary headache disorders can be associated with photophobia, eye pain, dry eye, autonomic features, and anisocoria. Conclusions: Patients with primary headache disorders may experience a wide range of visual and ophthalmic symptoms. An understanding of the typical features of these disorders allows providers to help patients find appropriate treatment without unnecessary testing and to recognize when atypical presentations require additional evaluation.